THE EFFECT OF MODERNIZATION OF MAIN EQUIPMENT OF BEKANG BATTALION DEFENSE SYSTEM ON THE PREPARATION OF LOGISTIC SUPPORT FOR INDONESIAN ARMY - Wijayanto, Boby; Ismurdianto, Nanang Eko; Kusuma, Andyka (Jurnal Pertahanan dan Bela Negara, 2019)
The Unitary State of the Republic of Indonesia is one of the countries with a strategic path to world trade, and this has become a favorable supporting factor in various sectors in Indonesia. The territory of the Unitary Republic of Indonesia, which is also very broad, has implications for national defense that is complex and very open so that it is easily entered by anyone from various directions. The territory of the Republic of Indonesia consists of 7.7 million km2, stretching from Sabang to Merauke, from P. Miangas to P. Rote consisting of 17,504 islands united by vast seas and oceans. The problem that arises now is where the Army defense equipment especially in the Bekang Battalion is old and ineffective in supporting logistical activities. However, technically, the modernization of the Army defense equipment prior to comprehensive considerations, mainly based on the effectiveness of activities that can support the main tasks and the use of defense equipment in an effective and efficient operation, besides that in terms of modernizing military equipment and weapons in addition to supporting logistical activities, they must also be able to be tested in Combat Proven. In fulfilling modern defense equipment, it is highly expected to support the main tasks of the Army, especially support for defense equipment in the Bekang Battalion, the fulfillment of modern logistical transport vessels. This study analyzes the effect of modernization of the Bekang Battalion defense system on the readiness of the Army logistical support with a research sample in the Bekang Battalion Unit of the Army with data analysis using the SPSS (Statistical Package for Social Sciences) method to obtain an objective assessment of the effect of the readiness of the support units of the data analysis on the basic tasks of the Army. With the modernization of defense equipment, it is hoped that Battalion's readiness can be maximized in carrying out its duties in the future. Keywords: defense equipment, modernization, logistics, SPSS (Statistical Package for Social Science)